Anxiety Level and Academic Achievement of Medical Students at Universitas Muhammadiyah Jakarta - Nadia Rachmawati; Mohammad Labib (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2026)
Background: Academic achievement reflects students’ learning progress. Anxiety is an internal factor that may hinder learning and examination performance. The COVID-19 pandemic has been a significant stressor affecting students’ mental health. Purpose: This study aims to determine differences in academic achievement among medical students of the Faculty of Medicine and Health, Muhammadiyah University of Jakarta, class of 2020, based on anxiety levels. Methods: This cross-sectional analytical study involved 134 students selected through total sampling. After excluding incomplete responses, 121 students were included in the final analysis. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS), and Grade Point Average (GPA) data were obtained from institutional records. Data were analyzed using the Kruskal–Wallis test to examine differences in GPA across anxiety level categories. Results: Most students experienced very severe anxiety (51.6%). The highest mean GPA was observed in the no-anxiety group, while the lowest was found in the severe anxiety group. The Kruskal–Wallis test showed a statistically significant difference in GPA across anxiety levels (p = 0.019). Conclusion: There was a statistically significant difference in academic achievement across anxiety levels. Higher anxiety levels were associated with lower GPA among medical students during the COVID-19 pandemic.